Cetuximab with radiotherapy as an alternative treatment for advanced squamous cell carcinoma of the temporal bone. Issue 3 (June 2018) - Ebisumoto, Koji; Okami, Kenji; Hamada, Masashi; Maki, Daisuke; Sakai, Akihiro; Saito, Kosuke; Shimizu, Fukuko; Kaneda, Shoji; Iida, Masahiro
Abstract: The prognosis of advanced temporal bone cancer is poor, because complete surgical resection is difficult to achieve. Chemoradiotherapy is one of the available curative treatment options; however, its systemic effects on the patient restrict the use of this treatment. A 69-year-old female (who needed peritoneal dialysis) presented at our clinic with T4 left external auditory canal cancer and was treated with cetuximab plus radiotherapy (RT). The primary lesion showed complete response. The patient is currently alive with no evidence of disease two years after completion of the treatment and does not show any late toxicity. This is the first advanced temporal bone cancer patient treated with RT plus cetuximab. Cetuximab plus RT might be a treatment alternative for patients with advanced temporal bone cancer.